Efficiency Analysis of Open Polygon Method in Land Mapping in Mojoroto Kediri - Nurcahyono, Nurcahyono; Mustofa, Imam; Fatima, Brenda; Pratama, Satrya Adi; Setyoningrum, Tyas Dwi; Salsabila, Fitri Amalia; Putri, Karisma (CIVED, 2024)
In the building establishment process, the geotechnical characteristics of soil have a significant impact on the structural performance of buildings. Therefore, soil mapping becomes a critical step in understanding the properties of soil that can affect foundation and structural stability. The mapping method used is open polygon mapping, which allows flexibility in determining land boundaries. Measurements were taken at three survey points: roadside, middle of the field, and edge of the field. The mapping results reveal variations in soil characteristics that need to be considered in development planning to ensure solid and stable building foundations. The implementation of Geographic Information Systems (GIS) in this process facilitates deeper data analysis and better visualization of field conditions. The mapping results show significant variations in ground elevation at each survey point, emphasizing the importance of understanding the area's topography. Additionally, area measurements were conducted using open polygon data, providing fundamental information for area development planning. Contour maps generated through Surfer software provide clear visualization of ground elevations at each survey point, enhancing understanding of the area's topography. This research contributes significantly to understanding soil characteristics and topography in the rear area of Mojoroto. It is expected to serve as a guide for area development planning, ensuring the stability and safety of future building structures. Thus, soil mapping is a critical step in ensuring the safety and sustainability of future buildings and contributes to sustainable area development planning.